Upregulation of SOX11 enhances tamoxifen resistance and promotes epithelial‐to‐mesenchymal transition via slug in MCF‐7 breast cancer cells. Issue 10 (11th February 2020) - Xiao, Yingsheng; Xie, Qin; Qin, Qingsong; Liang, Yuanke; Lin, Haoyu; Zeng, De
Abstract: Resistance to tamoxifen remains a prominent conundrum in the therapy of hormone‐sensitive breast cancer. Also, the molecular underpinnings leading to tamoxifen resistance remain unclear. In the present study, we utilized the Gene Expression Omnibus database to identify that SOX11 might exert a pivotal function in conferring tamoxifen resistance of breast cancer. SOX11 was found to be markedly upregulated at both the messenger RNA and protein levels in established MCF‐7‐Tam‐R cells compared to the parental counterparts. Moreover, SOX11 was able to activate the transcription of slug via binding to its promoter, resulting in promoting the progress of epithelial‐to‐mesenchymal transition and suppressing the expression of ESR1. Downregulating SOX11 expression can restore the sensitivity to 4‐hydroxytamoxifen in MCF‐7‐Tam‐R cells. Survival analysis from large sample datasets indicated that SOX11 was closely related to poorer survival in patients with breast cancer. These findings suggest a novel feature of SOX11 in contributing to tamoxifen resistance. Hence, targeting SOX11 could be a potential therapeutic strategy to tackle tamoxifen resistance in breast cancer. Abstract : SOX11 can promote the epithelial–mesenchymal transition process and enhance tamoxifen resistance in MCF‐7 cells. Hence, targeting SOX11 could be a potential therapeutic strategy to tackle tamoxifen resistance in breast cancer.